FORECAST ANALYSIS OF THE NUMBER OF MARINE PASSENGER LEVELS SEEN FROM TREND COMPONENTS USING TIME SERIES DATA AT PT. CITRABARU ADINUSANTARA - Sofia, Susetyowati -; Putri, Clara Tania; Lewenussa, Ramli -; -, Rokhimah - (BALANCE: JOURNAL OF ISLAMIC ACCOUNTING, 2024)
PT. Citrabaru Adinusantara is a company engaged in the field of sea transportation services in Southwest Papua. This company provides commercial sea transportation services or pioneering shipping vessels, to shorten the distance of passenger and sea cargo traffic and guarantee the distribution of logistics to remote, undeveloped areas in Eastern Indonesia. The purpose of this research was to find out the forecasting level for the number of KM. Sabuk Nusantara 56 passengers the trend component at PT. Citrabaru Adinusantara in 2019-2022 with Time Series Analysis. Meanwhile, the type of research used is quantitative descriptive analysis. Based on the values ​​that have been processed using the POM QM For Windows application, it is known that forecasting based on time series analysis using the moving average method has a value of MAD = 122.028 passengers, MSE = 24870.79 passengers, and MAPE = 63.47% and the forecasting value for the next period is 154, 5 passengers.